Temperature dependence of IR exciton emission spectra in Müller cell intermediate filaments - Khmelinskii, Igor (2022)
Temperature dependences of IR exciton properties in Muller cell (MC) intermediate filaments (IFs) isolated from porcine retina were studied. It was found that the widths of the spectral emission bands in the 2500 cm-1 and 5000 cm-1 energy ranges grow with temperature. It was found that temperature effects on the bandwidth may be described by thermal activation of the low-frequency vibrational modes of the IFs. The average activation energies for the two IR bands were estimated. Considering the dynamics of IR emission, its buildup time was independent on the sample temperature, while its decay time decreased with temperature. Thus, the emission decay rate increased exponentially with the sample temperature. The mechanisms explaining the observed temperature effects were proposed and discussed. Taking into account that MC IFs are capable of transmitting ATP hydrolysis energy within and between cells, with these properties being apparently common for all IFs, these IFs may be used by cells for physical energy transport and communications. As presently reported, temperature effects upon IR exciton spectra should not affect these proposed physiological functions to any significant extent. Therefore, the currently reported data are important for improving our understanding of the physical communication mechanisms operating within and between cells.